Cardiac responses to hypoxia: the role of pyruvate dehydrogenase complex in carbohydrate utilisation - Handzlik, Michal (2016)
Accelerated carbohydrate utilisation and suppressed lipid oxidative metabolism are hallmarks of heart failure (HF). Hypoxia mimics failing heart metabolic reprogramming and has been suggested to play a role in cardiac metabolic switch. One aspect of the regulation of cardiac energy metabolism is the pyruvate dehydrogenase complex (PDC). Hypoxia inducible factor (HIF) signalling is thought regulate hypoxia-induced adaptations. HIF transcriptional activity is controlled by prolyl hydroxylase domain (PHD) protein and factor inhibiting HIF (FIH-1). In chapter 3 revealed that relative to baseline, acute hypoxia increased cardiac lactate efflux and suppressed fatty acid oxidation (FAO) rates in non-treated isolated mouse hearts with final cardiac recovery being 63% of baseline values. Hypoxic and post-hypoxic PDC activation, via dichloroacetate (DCA), decreased cardiac lactate release and FAO during reoxygenation, but failed to improve cardiac recovery relative to control hearts. Chapter 4 sought to establish how chronic hypoxia (11%) upregulates cardiac glycolytic flux, determined via 3H-glucose. Findings of this chapter indicate that of four enzymes considered to set the pace of glycolysis, upregulated pyruvate kinase (PK) flux, appears to explain accelerated hypoxia-induced cardiac glycolytic flux. Western blotting analysis revealed increased PK M2 protein isoform. Sustained hypoxia increased pentose phosphate pathway (PPP) flux, but left lactate accumulation unaltered. Chapter 5 examined the role of sustained in vivo hypoxia in modulating cardiac tolerance to subsequent acute H/R injury and chronic PDC activation in modifying hypoxic heart tolerance to acute injury. Chronic hypoxia reduced cardiac tolerance to H/R injury accompanied by increased glycolytic flux and lactate efflux during reoxygenation injury. Chronic PDC activation improved hypoxic heart tolerance to the acute injury and normalized cardiac metabolic flux and reduced tissue lactate accumulation during reoxygenation, indicative of increased carbohydrate oxidation. Collectively, the data appear to imply that forced carbohydrate oxidation normalizes hypoxic heart recovery from acute injury. In chapter 6 we demonstrated that global FIH-1 deletion increased isolated heart glycolytic flux at baseline and during reoxygenated. FIH-1 KO hearts displayed increased reoxygenated hexokinase (HK) and PK activities, but no changes in PK protein isoforms. Functional analysis revealed that FIH-1 deficiency does not affect isolated heart function at baseline and in response to acute injury. Acute PDC activation does not appear to improve cardiac function during acute hypoxic stress. Conversely, chronic PDC activation normalized, via restored metabolic flux, cardiac tolerance to acute injury following sustained in vivo hypoxia. Furthermore, the present thesis revealed increased PPP flux following sustained in vivo hypoxia, and proposed a pivotal role PKM2 may play in the regulation of hypoxic heart carbohydrate metabolism. In addition, we identified FIH-1 as a novel regulator of cardiac carbohydrate metabolism at baseline and following acute hypoxic injury.